Dual‐Polymer‐Electrolytes: High Voltage Stable Polyoxalate Catholyte with Cathode Coating for All‐Solid‐State Li‐Metal/NMC622 Batteries (Adv. Energy Mater. 42/2020). Issue 42 (10th November 2020) - Pan, Xiangyu; Sun, Han; Wang, Zhaoxu; Huang, Hao; Chang, Qian; Li, Junpeng; Gao, Jian; Wang, Shaofei; Xu, Henghui; Li, Yutao; Zhou, Weidong
Abstract : In article number 2002416, Weidong Zhou and co‐workers develop a poly‐oxalate/poly‐ether dual‐polymer‐electrolyte system to electrochemically tolerate both high potential cathodes and low potential anodes, respectively. Combined with a cathode coating, the interfacial decomposition of poly‐oxalate in LiNi0.6 Mn0.2 Co0.2 O2 (NMC622) is suppressed. With the help of this strategy, the cycling performance of all‐solid‐state Li‐metal/NMC622 cells is significantly improved.